Model Sosialisasi Dan Pendampingan Mahasiswa KKP UIN Mataram Di Tengah Pandemi Covid 19 - M. Harja Efendi (Prodi Tadris Matematika-UIN Mataram, 2021)
Covid-19 is a disease caused by a new type of corona virus that appeared at the end of 2019 for the first time in Wuhan, China which is currently causing a pandemic in almost all over the world. The main symptoms of Covid-19 are cough, fever and shortness of breath (Ministry of Health, 2020). Covid-19 infection also causes quite high mortality in various countries. The Covid-19 pandemic which is currently endemic to the world is currently paralyzing all sectors including the world of education, where children have to carry out distance learning activities carried out at their respective homes via the internet. This creates new problems where some areas have not been reached by internet facilities. Online learning that has not been properly prepared certainly has an impact on the learning methods used by educators. Likewise, the acceptance of learning from students is also very diverse, often they do not understand the material or delivery from the teacher. The Minister of Education and Culture, Nadiem Makarim, together with 3 other ministers, namely the Minister of Religion, the Minister of Health and the Minister of Home Affairs, made an agreement to allow face-to-face schools starting in January 2021. Higher education as an institution that has the responsibility to be able to provide knowledge to the community should carry out Community Service activities as a form of the tri dharma of higher education